2013
DOI: 10.1186/2191-1991-3-29
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequencing: a systematic review of health economic evidence

Abstract: Recently the sequencing of the human genome has become a major biological and clinical research field. However, the public health impact of this new technology with focus on the financial effect is not yet to be foreseen. To provide an overview of the current health economic evidence for genome sequencing, we conducted a thorough systematic review of the literature from 17 databases. In addition, we conducted a hand search. Starting with 5 520 records we ultimately included five full-text publications and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 23 publications
0
48
0
Order By: Relevance
“…cost per megabase/run) that are not linked to specific clinical applications were not included, as an earlier review summarizes these costs for different sequencing platforms. 13 Search strategies and study selection Search strategies were designed for EMBASE, MEDLINE, the Cochrane Library, EconLit, and the University of York Centre for Reviews and Dissemination (CRD) Database. These strategies included both index terms and free-text words (see Supplementary Appendix S1 online).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…cost per megabase/run) that are not linked to specific clinical applications were not included, as an earlier review summarizes these costs for different sequencing platforms. 13 Search strategies and study selection Search strategies were designed for EMBASE, MEDLINE, the Cochrane Library, EconLit, and the University of York Centre for Reviews and Dissemination (CRD) Database. These strategies included both index terms and free-text words (see Supplementary Appendix S1 online).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the substantial reductions in sequencing costs following these developments, there is still little information available on the costs of bioinformatics analysis and clinical interpretation (and on what the costs of sequencing are, if not done at scale), as documented in earlier literature reviews. [11][12][13] It is therefore important to understand what economic evaluation evidence is currently available in the literature on clinical applications of WES and WGS, and where there are gaps in the evidence base.…”
Section: Introductionmentioning
confidence: 99%
“…These differences are caused by the large differences in the number of bases sequenced, affecting both consumable price and annual throughput of the NGS systems. Whereas with WGS the entire genome is sequenced, WES sequences only the protein-coding parts (exons), which constitute approximately 1%-2% of the genome (8,20,28 ). The sensitivity analyses showed that future cost reductions are most likely to occur if consumable costs decrease considerably.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques have not only proven to be promising tools in studying the genetics underlying rare Mendelian disorders (12)(13)(14), but have also been shown to be valuable diagnostic tools in genetic diseases (3,8,(15)(16)(17)(18)(19). A recent review showed that although several studies on the cost-effectiveness of NGS applications have been performed, a complete and valid cost overview is currently lacking (20 ). Moreover, the costs for the sequencing process itself might be only a small part of the total costs.…”
mentioning
confidence: 99%
“…As sequencing becomes more widespread, new costs such as data management or computationally-intensive analysis will continue to emerge (Sboner et al, 2011). Two literature reviews reveal a lack of high-quality economic data and thus the inability to form any conclusions with regard to the cost of expanding genomic research (Frank et al, 2013;Gordon et al, 2014).…”
Section: (Vi) Reimbursementmentioning
confidence: 98%